2008
DOI: 10.1136/gut.2007.145177
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-oesophageal reflux symptoms, oesophagitis and Barrett's oesophagus in the general population: the Loiano-Monghidoro study

Abstract: GORD is common in Italy, but the prevalence of Barrett's oesophagus in the community is lower than has been reported in selected populations. Both frequent and infrequent reflux symptoms are associated with an increased risk of oesophagitis. Individuals with oesophagitis and Barrett's oesophagus often have no reflux symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
280
2
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(321 citation statements)
references
References 29 publications
27
280
2
12
Order By: Relevance
“…BE has been detected in ∼ 15% of patients with chronic GERD ( 26 ) and in ∼ 1-2% of population subjects ( Table 2 ) ( 27,28 ). In a population-based study from Sweden, the authors found that severe and chronic GERD were risk factors for the development of EAC; however, 40% of the cohort with esophageal cancer reported no prior history of GERD symptoms ( 29 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…BE has been detected in ∼ 15% of patients with chronic GERD ( 26 ) and in ∼ 1-2% of population subjects ( Table 2 ) ( 27,28 ). In a population-based study from Sweden, the authors found that severe and chronic GERD were risk factors for the development of EAC; however, 40% of the cohort with esophageal cancer reported no prior history of GERD symptoms ( 29 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In a Swedish prospective study by Ronkainen et al (5), an upper endoscopy was performed on a random sample of 1000 adults, detecting BE in 16 individuals (1.6%), of whom only 5 were considered o have LSBE (0.5%). Similarly, population-based studies from Italy and China showed a BE prevalence of 1.3% and 1.9%, respectively (7,8). On the other hand, in a prospective study that included 961 colonoscopy patients (mean age=-59 years) who underwent additional EGD, an overall BE prevalence of 6.8% was observed, with the majority (5.5%) having SSBE in those aged 40 years or more irrespective of any previous episodes of heartburn (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these limitations, our findings are in accordance with population-based studies from various Western nations. 3,7,18,24,[34][35][36] In summary, there are marked differences in the country specific prevalence of UGI complaints. These differences are associated with socioeconomic indicators such as the GDP per capita.…”
Section: Discussionmentioning
confidence: 99%